1999
DOI: 10.1136/vr.145.25.721
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of sarcoptic mange from a Belgian pig breeding farm with a combination of injectable and in‐feed ivermectin

Abstract: Sarcoptes scabiei var suis was eradicated from a Belgian pig farm by using a combination of injections of ivermectin and ivermectin in the feed. The detection of mites in ear scrapings, and calculations of an average dermatitis score and a scratching index were used to evaluate the mange status of the pigs before and after the treatment. Before the treatment 28 per cent of ear scrapings of finishers were positive for the presence of mites, their average dermatitis score (ADS) was 0.92 and their scratching inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The aim of both the traditional ‘targeted’ (selective) and ‘non‐targeted’ (whole‐herd) treatment strategies is to prevent the piglets from mite infestation, but the infestation is usually kept at a subclinical level in the farm. However, only the whole‐herd treatment strategy with at least two treatments at an interval of 2 weeks enables, in principle, an eradication of sarcoptic mange from a farm (Jacobson et al ., 1999; Smets et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of both the traditional ‘targeted’ (selective) and ‘non‐targeted’ (whole‐herd) treatment strategies is to prevent the piglets from mite infestation, but the infestation is usually kept at a subclinical level in the farm. However, only the whole‐herd treatment strategy with at least two treatments at an interval of 2 weeks enables, in principle, an eradication of sarcoptic mange from a farm (Jacobson et al ., 1999; Smets et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the test, however, makes it insufficient for use as the only tool. According to findings in other studies [22,17] a rubbing index at or above 0.4 may be found even in mange-free herds. A seasonal variation has been suggested [17] with a higher index recorded during the summer months.…”
Section: Discussionmentioning
confidence: 56%
“…In conclusion, a 2-injection strategy which has been used successfully under field conditions for many years [10,12,18,19,14,7,21,15,22] seems to be the most effective method, when using ivermectin. According to this study, the results from an experimental trial [6] and results reported in a field trial [17], the single injection strategy is effective when using doramectin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exception is the control of mange; S. scabiei has no long-lived environmental stage and relies on direct contact for transmission, so systematic application of acaricides can effectively reduce infection and stamping out the parasite on a farm is possible when quarantine measures and proper diagnostic screening are in place (e.g. [38]). However, sustainability is jeopardized by the development of acaricide resistance as reported from human scabies [22].…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%